IMPLEMENTASI PENILAIAN AUTENTIK PADA RANAH PSIKOMOTORIK DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR - Peni Nur Syamsiah; Andi Prastowo (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
The symptoms that have occurred so far are of the view that PAI teachers in the assessment only focus on affective and cognitive aspects, this causes the psychomotor domain to be ignored so that special attention needs to be given. Assessment for the psychomotor domain is basically one of the important aspects of the skills that are required to be evaluated in the learning process. This study aims to examine the implementation of authentic assessment in the psychomotor domain contained in PAI learning at SDN 01 Ujan Mas, Kepahiang Bengkulu Regency. The approach used in this research is descriptive qualitative with the type of research used is field research with research located at SDN 01 Ujan Mas, Kepahiang Regency, Bengkulu. The informants in this study were PAI teachers at SDN 01 Ujan Mas, Kepahiang Regency, Bengkulu. In relation to the data collection method, in this study the researchers used the interview, observation and documentation methods. In this study, the data analysis technique used by the researcher is reduction, data display and conclusion drawing and for the validity of the data using triangulation techniques. The result of this study is that the implementation of authentic assessment in the psychomotor domain in PAI learning, which is divided into PAI assessment planning for the psychomotor domain, has been carried out well. The implementation of the assessment in the psychomotor domain uses various techniques including practical techniques, for example in discussing the subject matter of worship related to prayer as well as for the instruments used in the assessment that are relevant to what has been designed. For processing the assessment is carried out in the form of numbers which is then followed up on the value obtained in the form of remedial for students who have not completed.